Design and validation of a psychoeducational manual on port catheter placement in women with breast cancer - Bonilla López, Leilani Aniela; Ortiz Rangel, Valeria Guadalupe; Lugo González, Isais Vicente (Psicooncología, 2024)
Introduction: Educational approaches are recommended interventions to address the informational and emotional needs of patients with breast cancer. Among them are psychoeducational materials, which ideally should be evidence-based developed, to promote health literacy; however, this is rare. Objective: Design and validate the content of a psychoeducational manual on central venous catheters in women with breast cancer, as well as analyze its level of readability. Method: a prospective and transversal-descriptive research was carried out, through a non-experimental design. To evaluate the manual, 9 expert judges in psycho-oncology, intravenous therapy and medicine participated. Content validity was analyzed with the Osterlind index and reading difficulty with the INFLESZ index. Results: The manual obtained an excellent evaluation of its content with an Osterlind index of 0.88 and in the analysis of reading difficulty it obtained a score of 67.3, evidence of very easy-toread material. Conclusions: The findings show that the developed manual is of quality, easy to access and understand for patients who will undergo central venous catheters. Likewise, evidence is offered of the importance of building educational materials based on research and statistical indicators.
Keywords: Validation study; teaching materials; breast neoplasms; central venous catheters